PENGEMBANGAN BUNDLE DALAM MENURUNKAN URINARY TRACT INFECTION (UTI) DI RSUD SEJIRAN SETASON MUNTOK - Ani Syafriati; Elsye Maria Rosa; Novita Kurnia Sari (MEDIA ILMU KESEHATAN, 2018)
Background: Development of CAUTI bundle is very important to evaluate the nurse in implementing nursing practice related to urinary catheter which is one of prevention efforts and risk control of CAUTI. Objective: The purpose of this study is to develop CAUTI bundle that is adjusted to hospital condition in Sejiran Setason Muntok Hospital. Methods: In this study used qualitative method by conducting indepth interview and focus group discussion (FGD). It conducted for 3 weeks in Sejiran Setason Muntok Hospital, the total sample are 22 participants. The result produced the themes that used as the material for the development of the bundle or the observation sheet of CAUTI. Results: There are 10 themes which become material for the development of CAUTI bundle. The CAUTI Bundle consists of bundle components such as indication of urinary catheter insertion, urinary catheter installation must comply with SOP, monitoring of urine output by regularly, emptying urine bag regularly, performing hand hygiene before and after procedure, using masks and handscoons, patients and families must be aware of their role in minimizing the risk of CAUTI. Conclusion: Development of the bundle is very important as one of prevention of CAUTI incident in hospital. Keyword : Bundle, CAUTI, Development.